Examination of the law of evidence relating to rape trials / Noorhajran Mohd. Noor - Mohd. Noor, Noorhajran (Faculty of Law, 1985)
One of the main tasks of the past decade for women has been to get the world at large, to take times of several violence against women seriously. Violence against women has increased and is spiralling Rape is an act of violence against women. It is a hostile and a sadistic act. It is a violation of a women's autonomy and a negation of her independence